The Effects of internal migration on first labor market outcomes from college graduates - CHOI, Da Hee (KDI School, 2021)
Half of Korea’s population has been concentrated in the Seoul metropolitan area since 2020 with an earlier concentration of young people and this phenomenon is expected to continue. In this paper, I analyze the effect of internal migration from college graduates on their first labor market outcomes in terms of job status, being employed in a large-sized company, and average monthly income by using five-year Graduates Occupational Mobility Survey. The results show that migration has positive impact on labor outcomes even after matching samples using propensity scores to reduce selection bias issues. However, the estimates on being workers in large-sized companies do not present statistically significant. The results from sub-groups analysis show that labor outcomes from migration may vary depending on the direction of movement. This study suggests that youth outflow could continue if locals fail to clarify reasons of migration from youth and create decent jobs with residential policies.
Thesis(Master) -- KDI School: Master of Development Policy, 2021
Keywords: Migration, Internal; Labor market--Korea (South)